Education in the Post-Reform Era: new Educational Realities of Russia - Danilchenko S. L. (The Development of Modern Education in the Context of Pedagogical Competenciology, 2022)
The implementation of bourgeois reforms, the abolition of serfdom were an objective incentive for the acquisition of knowledge by the most numerous class of Russian society - the peasantry. A major role in the development of primary education was played by three-year zemstvo schools, created with modest funds from the local budget and donations from ascetics. Under the influence of the rapid development of the economy, the state is taking the most important step in the secondary education system - making the transition from real classes to real gymnasiums. The post-reform era is a time of successful development of pedagogical science.
Keywords: разработка; начальное образование; primary education; проведение буржуазных реформ; отмена крепостного права; трехгодичные земские школы; переход от реальных классов к реальным гимназиям; обсуждение и принятие университетского устава 1863 года; педагогические периодические издания; труды ученых-педагогов; посвященные проблемам обучения и воспитания; the implementation of bourgeois reforms; the abolition of serfdom; three-year zemstvo schools; the transition from real classes to real gymnasiums; the development; discussion and adoption of the university charter of 1863; the development of pedagogical science; pedagogical periodicals; the works of scientists and teachers devoted to the problems of education and upbringing; развитие педагогической науки